Evaluation of the Efficacy of Grape Extracts on Hematological Parameters in Rats with Induced Leukemia - ibrahim al hassan, Rahma naktal wali; Hameed, Hamza N (American Journal of Biomedicine and Pharmacy, 2025)
Leukemia (blood cancer) is a serious disease that affects the bone marrow and leads to the production of large quantities of immature blood cells called blast cells. These cells do not function normally and crowd out healthy cells, leading to weakened immunity, anemia, and easy bleeding, In this study, leukemia was induced in a group of rats (experimental animals) They were then treated with natural substances extracted from grape skins, such as protein precipitate and fatty acid, in addition to methoxate, a chemotherapy drug used in cancer treatment. After treatment, blood smears were taken from these rats and examined under a microscope to determine the extent of the disease The results showed that some natural extracts had a clear effect in reducing cancer cells and improving blood formation.